ANALISIS DAYA DUKUNG TANAH PEMBANGUNAN PONDOK PESANTREN RIBAT AS SYA’ADI TAEH BARUAH KABUPATEN LIMA PULUH KOTA - Asnur, Hanifah; Yunita, Rini; Dilson, Dilson (Ensiklopedia of Journal, 2022)
The topography of the Regency of Fifty Cities which varies between flat, undulating and hilly is one of the factors that can cause foundation failure if there is no proper foundation type planning. The construction of the Ribath As Sa'ady Islamic Boarding School is one of the objectives of the RPJP (Long Term Development Plan) of Fifty Cities Regency, namely DP IV (settlement development area). To assist the government in realizing the RPJP, it is necessary to analyze the carrying capacity of the soil to determine the type of foundation that is suitable so that construction failure does not occur. This study uses the CPT (Cone Penetration Test)/sondir test to obtain the Conus Resistance Value (NK) parameter in Kg/cm2 units, and the amount of adhesive resistance (JHP) in Kg/cm units. The two parameters above are recorded for every 20 cm interval to a depth where the NK value is 160 kg / cm2, with a maximum depth limit of 13.80 m from the local soil surface, the recommended type of foundation is the type of deep foundation (Bore Pile)